Human endogenous retrovirus-K HML-2 integration within RASGRF2 is associated with intravenous drug abuse and modulates transcription in a cell-line model - Karamitros, T; Hurst, T; Marchi, E; Karamichali, E; Georgopoulou, U; Mentis, A; Riepsaame, J; Lin, A; Paraskevis, D; Hatzakis, A; McLauchlan, J; Lin, A; et al. (National Academy of Sciences, 2018)
HERV-K HML-2 (HK2) has been proliferating in the germ line of humans at least as recently as 250,000 years ago, with some integrations that remain polymorphic in the modern human population. One of the solitary HK2 LTR polymorphic integrations lies between exons 17 and 18 of RASGRF2, a gene that affects dopaminergic activity and is thus related to addiction. Here we show that this antisense HK2 integration (namely RASGRF2-int) is found more frequently in persons who inject drugs compared with the general population. In a Greek HIV-1–positive population (n = 202), we found RASGRF2-int 2.5 times (14 versus 6%) more frequently in patients infected through i.v. drug use compared with other transmission route controls (P = 0.03). Independently, in a United Kingdom-based hepatitis C virus-positive population (n = 184), we found RASGRF2-int 3.6 times (34 versus 9.5%) more frequently in patients infected during chronic drug abuse compared with controls (P ≺ 0.001). We then tested whether RASGRF2-int could be mechanistically responsible for this association by modulating transcription of RASGRF2. We show that the CRISPR/Cas9-mediated insertion of HK2 in HEK293 cells in the exact RASGRF2 intronic position found in the population resulted in significant transcriptional and phenotypic changes. We also explored mechanistic features of other intronic HK2 integrations and show that HK2 LTRs can be responsible for generation of cis-natural antisense transcripts, which could interfere with the transcription of nearby genes. Our findings suggest that RASGRF2-int is a strong candidate for dopaminergic manipulation, and emphasize the importance of accurate mapping of neglected HERV polymorphisms in human genomic studies.